The relationship between training and employee experience in PT.XYZ'S generation z employees during pandemic (Journal of Business and Management, 2022)
The business process has been changed due to Covid-19. The company should be able to provide their employee to develop their skills to run the business. The training was the method to help employees increase their knowledge and skills and improve their abilities. Employee experience is essential for a company to strive in the pandemic. The one who just join the workforce currently is generation Z. Indonesia is the world's largest palm oil producer. Palm oil is affected by the Covid-19 pandemic. Therefore, this research examines the palm oil company in Indonesia. The objectives of this research are to analyze the relationship between training and employee experience and analyze the most affecting training sub-factor towards employee experience. For training variables, this research uses the Kirkpatrick model and for the employee experience use the employee experience framework by Morgan. This research uses a quantitative approach with an online questionnaire. Data are collected and analyzed using regression. The research findings are there is a positive and significant relationship between training and employee experience, there is a positive and significant relationship between result and employee experience. The recommendation from this research covers all training aspect, and result to have a good employee experience.